Synthesis and Spectroscopic Studies of Mixed Ligand Complexes of Transition Metals with a Proton Pump Inhibitor and RNA Bases - Verma, Sarika; Shrivastva, Sarita (Asian Journal of Chemistry, 2012)
Few mixed ligand complexes of transition metals have been synthesized by reacting their metal salts with aproton pump inhibitor namely lansoprazole and RNA bases adenine. All the complexes were synthesized in ethanolic medium and refluxed in reaction medium (1:1:2, M:L:L2 ratio). The yield percentage ranging from 80-90 %. The complexes are coloured solids and of the type (Llanso·M·(LAde)2·xH2O)X·nH2O and X can be SO4. They are characterized through elemental analyses, conductance measurements, spectroscopy (IR, Mass, 1H NMR and UV). An IR spectrum indicates that all the ligands behave as bidentate ligand. Molar conductance studies indicates electrolytic behaviour of these complexes. Metal complexes have been screened for their antibacterial activity towards P. arugenosa bacteria. The result reveals that the metal chelates showed more resistance as compared with parent drug.